PENGARUH PENGGUNAAN MODEL TWO STAY TWO STRAY TERHADAP HASIL BELAJAR TEMATIK DI SEKOLAH DASAR - Dewi Suci Utari; Kartono Kartono; Asmayani Salimi (Universitas Tanjungpura, 2020)
AbstractThe study aimed to analyze the influence of Two Stay Two Stray model on thematic learning outcomes of students of grade V state primary school 56 Pontianak west and to analyze how much influence Two Stay Two Stray model has on thematic learning outcomes of students of grade V state primary school 56 Pontianak west. The research method use experiment a from of quasi experimental design type non equivalent group design. Data collection technuiq are measurements with reseach instrumen in the from of multiple choice test to measure student learning out comes. Reseach population of all students of grade V state primary school 56 Pontianak west which amount to 98 are VB and VC class students 62 V class state primary school 56 Pontianak west. Based on calculation obtained, then the avarage study result of the students of the control class was 64,93 and the experiment were 69,7 based on result of the test calculation obtained 2,682 > 1,996 then Ha is accept. This sugests that there are differences in learning outcomes of studentsof control classes with experimentation classes. From the calculation of the Effect Size obtained 0,50 by medium criteria. This means there is an influence of the Two Stay Two Stray learning model on the themaatic learning result of students grade V state primary school 56 Pontianak west. Keywords: Influence, Study result ,Two Stay Two Stray Models